Exploration Of BPJS Health Patients' Experiences In Accessing Primary Health Services - Nurul Izzah; Makhrajani Majid; Nur linda; Ayu Dwi Putri Rusman; Rasidah Wahyuni Sari (Universitas Muhammadiyah Ponorogo, 2026)
Primary healthcare services are the initial access point for BPJS Kesehatan participants in the Indonesian healthcare system. However, the public still complains about various obstacles such as limited facilities, long waiting times, limited medication, and suboptimal healthcare services. This study aims to explore the experiences of BPJS patients in accessing services at the Lapadde Community Health Center in Parepare City. This study used a qualitative phenomenological approach through in-depth interviews with 16 informants. Data analysis was conducted using MAXQDA with coding and thematic methods. The results showed that patients considered the facilities inadequate, especially medical equipment and room comfort. Long waiting times were due to limited staff and high number of visits. Medication services were carried out according to procedures, but the types and stock were limited. Healthcare workers were considered friendly and communicative, although interaction was limited due to queues and limited human resources. In conclusion, BPJS patients still face obstacles in primary care, so improvements in facilities, queue management, medication availability, and communication training for healthcare workers are needed to support responsive and quality services.